Dimensionamento da força de trabalho como uma ferramenta de gestão - Primo, Francisco Caniçali (2018)
Objective: To develop a methodology for dimensioning the workforce in a higher education federal institution. Methodology: This is a methodological study developed at the Federal University of Espírito Santo - UFES. The data was collected from a set of documents generated by two committees that worked in the attempt to elaborate a method adjusted to the reality of UFES. For the development of the methodology, applied methods were used in institutions that are similar to the university, as well as tools and management models. Result: As a product of the Professional Master's Degree, a proposal for a methodology for workforce dimensioning was elaborated, consisting of seven steps, namely: organizational structure analysis, management model analysis, sector strategic planning, mapping of competencies, mapping processes, risk management and finally the quantitative calculation of the institution's workforce. Conclusion: The study contributes with the research developed in the area of Operations Management in the Public Sector in proposing a workforce dimensioning methodology for the Federal University of Espírito Santo, for it can be used as a vector of change, directing strategies, operations and actions to be carried out aiming at the constant improvement of the services delivered to the community through the development and improvement of the public institution.